How would you prove convergence/divergence of the following series?

$$\sum\limits_{n\geq 1}\dfrac{1}{(3n-1)(3n+1)}$$ I'm interested in more ways of proving convergence/divergence for this series.

My thoughts:

$$\sum\limits_{n\geq 1}\dfrac{1}{(3n-1)(3n+1)}$$

I'm going to use Integral Test

let $f(n)=\dfrac{1}{(3n-1)(3n+1)}$

we note that $f$ is a continuous, positive and decreasing function on the interval $[1,+\infty ($ then

$$\sum_{n=1}^\infty f(n) \text{ Convergent } \iff \int_1^\infty f(x)\,dx \text{ Convergent }$$

so let's try to compute $$\int_1^\infty f(n)\,dn=\int_1^\infty \dfrac{1}{(3n-1)(3n+1)}\,dn $$

Substitution for $n=\dfrac{1}{3}u$ and $dn=\dfrac{1}{3}du$ we got :

\begin{align} \int_1^\infty f(n)\,dn &=\int_1^\infty \dfrac{1}{(3n-1)(3n+1)}\,dn \\ &=\int_1^\infty \dfrac{1}{(3(\dfrac{1}{3}u)-1)(3(\dfrac{1}{3}u)+1)}\,\dfrac{1}{3}du \\ &=\dfrac{1}{3}\int_1^\infty \dfrac{1}{(u-1)(u+1)}\,du \\ &=\dfrac{1}{3}\int_1^\infty \dfrac{1}{(u^2-1)}\,du \\ \end{align} note that $\left(arctanh(u)\right)'=\left(\tanh^{-1}(h)\right)'=\dfrac{1}{1-u^{2}}$ so \begin{align} \int_1^\infty f(n)\,dn &=\dfrac{1}{3}\int_1^\infty \dfrac{1}{(u^2-1)}\,du \\ &=-\dfrac{1}{3}\int_1^\infty \dfrac{1}{(1-u^2)}\,du \\ &=-\dfrac{1}{3} \left(\tanh^{-1}(u)\right) \biggl|_{1}^{+\infty} \\ &=-\dfrac{1}{3} \left(\tanh^{-1}(3n)\right) \biggl|_{1}^{+\infty} \\ \end{align}

so can't go ahead beause i don't know the limit of $tanh^{-1}$ i can use woflrame to do that but suppose im in the contest what gonna do so my questions:

  • Is my proof correct
  • since the calculation is not easy in this case I'm interested in more ways of proving convergence/divergence for this series.
  • 1
    $\begingroup$ Another way to prove convergence: for $n > 1$ we have the inequalities $$\frac{1}{(3n-1)(3n+1)} < \frac{1}{(3n-1)^2} < \frac{1}{(3(n-1))^2}$$ so we can compare with $$\frac{1}{9}\sum_{n=2}^{\infty}\frac{1}{(n-1)^2}=\frac{1}{9}\sum_{n=1}^{\infty}\frac{1}{n^2}$$ which converges as a $p$-series with $p=2$. $\endgroup$ – Bungo Sep 22 '15 at 16:41
  • 1
    $\begingroup$ In the OP there is way too much work. And the first way is problematic, though fixable. Use Comparison with $\sum \frac{1}{8n^2}$ or Limit Comparison with $\sum \frac{1}{9n^2}$. $\endgroup$ – André Nicolas Sep 22 '15 at 16:42
  • 2
    $\begingroup$ The most direct proof is to note that $\sum_{n=1}^m\frac1{(3n-1)(3n+1)} $ = $\sum_{n=1}^m\left(\frac1{6n-2}-\frac1{6n+2}\right) $ $<\sum_{n=1}^m\left(\frac1{6n-3}-\frac1{6(n+1)-3}\right)=\frac13-\frac1{3m+3}$ by telescoping $\endgroup$ – Hagen von Eitzen Sep 22 '15 at 16:47
  • $\begingroup$ Or just show $1/(9n^2-1)\le 1/n^2$ for all $n.$ To the OP: You have $n$ in the integrals $dx;$ you should edit those. $\endgroup$ – zhw. Sep 22 '15 at 17:00
  • $\begingroup$ @zhw. thank u i fixed $\endgroup$ – Educ Sep 22 '15 at 17:06

There is an easier way to check convergence: $$0\leq \sum_{n\geq 1}\frac{1}{(3n-1)(3n+1)}\leq \sum_{n\geq 1}\frac{1}{8n^2}=\frac{\pi^2}{48}.$$ We may compute the value of the series by considering that: $$\begin{eqnarray*}\sum_{n\geq 1}\frac{1}{(3n-1)(3n+1)}&=&\frac{1}{2}\int_{0}^{1}\sum_{n\geq 1}\left(x^{3n-2}-x^{3n}\right)\,dx\\&=&\frac{1}{2}\int_{0}^{1}\frac{1+x}{1+x+x^2}\,dx\\&=&\color{red}{\frac{1}{2}\left(1-\frac{\pi}{3\sqrt{3}}\right)}.\end{eqnarray*}$$


Checking Convergence

Applying a Telescoping Series, we get $$ \begin{align} \sum_{k=1}^N\frac1{(3n-1)(3n+1)} &\le\sum_{k=1}^N\frac1{(3n-2)(3n+1)}\\ &=\frac13\sum_{k=1}^N\left(\frac1{3n-2}-\frac1{3n+1}\right)\\ &=\frac13\left(1-\frac1{3N+1}\right) \end{align} $$ Therefore, $$ \sum_{k=1}^\infty\frac1{(3n-1)(3n+1)}\le\frac13 $$

Evaluating the Sum

Using $(9)$ from this answer, $$ \begin{align} \sum_{n=1}^\infty\left(\frac1{3n}-\frac1{3n-1}\right) &=\frac13\sum_{n=1}^\infty\left(\frac1n-\frac1{n-1/3}\right)\\ &=\frac13H_{-1/3}\\[3pt] &=-\frac12\log(3)+\frac\pi{6\sqrt3}\tag{1} \end{align} $$ Subtracting $(8)$ from $(7)$ in that same answer gives $$ \begin{align} \sum_{n=1}^\infty\left(\frac1{3n}-\frac1{3n+1}\right) &=\sum_{n=1}^\infty\left(\frac1{3n}-\frac1{3n-2}\right)+\overbrace{\sum_{n=1}^\infty\left(\frac1{3n-2}-\frac1{3n+1}\right)}^{\text{telescoping series}}\\ &=\frac13\sum_{n=1}^\infty\left(\frac1n-\frac1{n-2/3}\right)+1\\ &=\frac13H_{-2/3}+1\\[3pt] &=-\frac12\log(3)-\frac\pi{6\sqrt3}+1\tag{2} \end{align} $$ Partial fractions and $(1)$ and $(2)$ yields $$ \begin{align} \sum_{n=1}^\infty\frac1{(3n-1)(3n+1)} &=\frac12\sum_{n=1}^\infty\left(\frac1{3n-1}-\frac1{3n+1}\right)\\ &=\frac12\left[\sum_{n=1}^\infty\left(\frac1{3n}-\frac1{3n+1}\right) -\sum_{n=1}^\infty\left(\frac1{3n}-\frac1{3n-1}\right)\right]\\[3pt] &=\frac12-\frac\pi{6\sqrt3}\tag{3} \end{align} $$

  • $\begingroup$ @ robjohn nice way $\endgroup$ – Educ Sep 22 '15 at 17:36

The method proposed is one way forward. To carry out the integration, we use partial fraction expansion to write

$$\begin{align} \int_1^{\infty}\frac{1}{(3x-1)(3x+1)}\,dx&=\int_1^{\infty}\left(\frac{1/2}{3x-1}-\frac{1/2}{3x+1}\right)\,dx\\\\ &=\left.\frac12\log\left(\frac{3x-1}{3x+1}\right)\right|_{1}^{\infty}\\\\ &=\frac12 \log 2 \end{align}$$

and conclude that the series converges.

At the request of the OP, we use limit comparison test to show convergence. We recall that


Since $$\lim_{n\to \infty}\frac{1/n^2}{1/(9n^2-1)}=9<\infty$$then the series of interest converges.

  • $\begingroup$ Could you also make it with taylor expanasion and Limit Comparison please $\endgroup$ – Educ Sep 22 '15 at 16:51
  • 1
    $\begingroup$ @Educ I added a section that uses the limit comparison test. I'm not sure what you are looking for with respect to using Taylor expansion. $\endgroup$ – Mark Viola Sep 22 '15 at 17:01

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.